An integrated system with multiple product lifecycles for remanufacturing (IS-MPLR): new opportunities and challenges. Issue 1 (2nd January 2021) - Li, Kai; Liu, Jing; Fu, Hong; Zhao, NengGui
ABSTRACT: The environmental and social impact of remanufacturing, as well as its economic value, have attracted widespread attention. Over the past three decades, the researches of the remanufactured product lifecycle management (RPLM) have focused on product design, product recycling networks, remanufacturing production, and closed-loop supply chains. However, a broader combination should be considered in the context of new information technology. The remanufacturable core can connect multiple products and form multiple life cycles. This triggers a new relationship of competition-cooperation among stakeholders in the supply chain, which is also a perspective for future research. In this paper, the authors first propose an integrated system with multiple product lifecycles for remanufacturing (IS-MPLR), which is composed of three parts. They are the integration between products and components, the integration among multiple products, and the integration of the entire closed-loop supply chain. Then a systematic literature review of the RPLM is undertaken, and the future research direction is prospected.